A Viral-Vectored Multi-Stage Malaria Vaccine Regimen With Protective and Transmission-Blocking Efficacies - Yusuf, Yenni; Yoshii, Tatsuya; Iyori, Mitsuhiro; Mizukami, Hiroaki; Fukumoto, Shinya; Yamamoto, Daisuke S.; Emran, Talha Bin; Amelia, Fitri; Islam, Ashekul; Syafira, Intan; Yoshida, Shigeto (Frontiers in Immunology, 2019)
Malaria parasites undergo several stages in their complex lifecycle. To achieve reductions in both the individual disease burden and malaria transmission within communities, a multi-stage malaria vaccine with high effectiveness and durability is a more efficacious strategy compared with a single-stage vaccine. Here, we generated viral-vectored vaccines based on human adenovirus type 5 (AdHu5) and adeno-associated virus serotype 1 (AAV1) expressing a fusion protein of the pre-erythrocytic stage Plasmodium falciparum circumsporozoite protein (PfCSP) and the transmission-blocking sexual stage P25 protein (Pfs25). A two-dose heterologous AdHu5-prime/AAV1-boost immunization regimen proved to be highly effective for both full protection and transmission-blocking activity against transgenic P. berghei parasites expressing the corresponding P. falciparum antigens in mice. Remarkably, the immunization regimen induced antibody responses to both PfCSP and Pfs25 for over 9 months after the boosting and also maintained high levels of transmission-reducing activity (TRA: > 99%) during that period, as evaluated by a direct feeding assay. If similar efficacies on P falciparum can be shown following vaccination of humans, we propose that this multi-stage malaria vaccine regimen will be a powerful tool for malaria control, providing greater overall protection and cost-effectiveness than single-stage vaccines.